Relationship between renal deposition of complement C3， IgG， IgM and pathology in IgA nephropathy - Fang-cao Lu; Hong-ling Yuan (Linchuang shenzangbing zazhi)
ObjectiveTo explore the effects of complement C3， IgG and IgM renal deposition on renal pathological injury in patients with IgA nephropathy.MethodsFrom August 1， 2019 to January 30， 2021， retrospective review was performed for electronic medical records of 119 patients with primary IgA nephropathy diagnosed by renal biopsy. They were divided into three groups according to Lee grading scheme. The differences of general profiles， laboratory parameters and pathological findings among three groups were compared. The independent influencing factors of pathological Lee grades were examined by Logistic regression. Glomerular immunoglobulin and complement deposition were evaluated by Lee grading scheme and Oxford pathological classification and their effects on renal injury examined.ResultsMultivariate Logistic regression analysis revealed that reductions of hemoglobin and albumin， elevated levels of serum creatinine， Scr， cystatin C， retinol-binding protein and complement C3 deposition were independent factors affecting the Lee grades of renal biopsy in IgAN patients. No correlation existed between serum levels of IgA， C3， IgM， IgG and the intensity of pathological deposition （P>0.05）. According to Oxford classification， the deposition rate of complement C3 2+~3+ was higher in M1/S1 group than that in M0/S1 group （P<0.05）. The positive rate of IgG deposition was higher in Oxford type E1 group than that in E0 group （P<0.05）.ConclusionHigh deposition of complement C3 in renal tissue promotes mesangial cell proliferation and glomerular segmental sclerosis or adhesion. The deposition of IgG in renal tissue IgAN may be correlated with cellular proliferation in glomerular capillaries. The deposition of IgM may be non-specific in renal tissue of IgAN patients.